Determinants of Stunting in Children Under Five in Pontianak City: A Systematic Literature Review - Uliyanti; Adha Panca Wardanu (Indonesian Journal of Administration and Health Research (IJAHR), 2025)
Stunting remains a significant public health issue in Pontianak City, with long-term impacts on children's growth and development. This study aims to identify the main determinants of stunting among children under five in Pontianak, determine the dominant contributing factors, and formulate evidence-based policy recommendations for more effective and context-specific interventions. A Systematic Literature Review (SLR) was conducted using articles from Google Scholar and Scopus, published between 2015 and 2024. Literature was retrieved using the keywords "Stunting" AND "Pontianak" via the Publish or Perish application and selected based on predefined inclusion and exclusion criteria. The dominant factors contributing to stunting include inadequate protein, calcium, phosphorus, micronutrient intake, infectious diseases (e.g., diarrhea), and poor household sanitation. Moderate factors include maternal height, young maternal age, Posyandu activity, exposure to cigarette smoke, and inappropriate complementary feeding. Some factors, such as exclusive breastfeeding and immunisation, showed mixed results across studies. Reducing stunting in Pontianak requires targeted nutritional interventions, improved sanitation, and strengthened community-based health services tailored to local contexts and supported by evidence-based strategies.Stunting masih menjadi masalah kesehatan serius di Kota Pontianak, dengan dampak jangka panjang terhadap pertumbuhan dan perkembangan anak. Penelitian ini bertujuan mengidentifikasi faktor-faktor utama penyebab stunting pada balita di Kota Pontianak, menentukan faktor dominan, dan merumuskan rekomendasi berbasis bukti untuk intervensi yang efektif. Studi ini menggunakan pendekatan Systematic Literature Review (SLR) dengan sumber artikel dari Google Scholar dan Scopus tahun 2015–2024. Literatur dicari menggunakan kata kunci “Stunting” AND “Pontianak” melalui aplikasi Publish or Perish, dan diseleksi berdasarkan kriteria inklusi dan eksklusi tertentu. Faktor dominan penyebab stunting meliputi rendahnya asupan protein, kalsium, fosfor, zat gizi mikro, infeksi (seperti diare), serta buruknya sanitasi rumah tangga. Faktor sedang meliputi tinggi badan ibu, usia ibu muda, keaktifan Posyandu, paparan asap rokok, dan pemberian MP-ASI. Beberapa faktor seperti ASI eksklusif dan imunisasi menunjukkan hasil yang bervariasi antar studi. Penurunan stunting di Pontianak memerlukan intervensi gizi spesifik, perbaikan sanitasi, dan penguatan layanan kesehatan masyarakat berbasis bukti dan konteks lokal.